A Force for Change The Class of 1950 (Purdue University Press, 1995)
Some of them were grown men going to college on the new G.I. Bill, and some were boys -- eighteen years old, straight out of high school. There were also young women coming to campus, rich in the traditions of their mothers and grandmothers. These women didn't know it, but the seeds of the modern women's movement had been planted during the war and in their generation. There were African-Americans who came to campus and found segregation and racial stereotypes, even after some of them had fought a war for freedom. This mixture of students blended together on the college campuses of America in the late 1940s and exploded into the world in 1950. Journalist John Norberg's illuminating oral history allows members of Purdue University's Class of 1950 to tell their stories in their own words. "(This is) a narrative that will hold special interest for those with Purdue or West Lafayette ties, but its scope is broad enough to interest a wider population".